2008
DOI: 10.1080/14636770701843675
|View full text |Cite
|
Sign up to set email alerts
|

The social uses of DNA in the political realm or how politics constructs DNA technology in the fight against crime

Abstract: Research has shown that the adoption and integration of new technologies in professional environments and daily lives depend less on their objective characteristics and "real" performance than on representations and hopes built into those technologies. This paper will focus on DNA technology and the meanings and expectations invested into it by actors who participated in the debate surrounding two bills on DNA identification in Canada. Through this process, we will uncover the symbolic conditions that allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The DNA-typing data can also be used in the investigative phase of the criminal investigation where suspects can be identified through a match in the national DNA database. DNA databases are often referred to as an efficient crime-fighting tool (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). It is, for example, shown that in the Netherlands 50% (6) and in the UK 59% (11) of the DNA crime traces result in a match with a person in the DNA database.…”
mentioning
confidence: 99%
“…The DNA-typing data can also be used in the investigative phase of the criminal investigation where suspects can be identified through a match in the national DNA database. DNA databases are often referred to as an efficient crime-fighting tool (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). It is, for example, shown that in the Netherlands 50% (6) and in the UK 59% (11) of the DNA crime traces result in a match with a person in the DNA database.…”
mentioning
confidence: 99%
“…An indicator that research on technology in criminology has not taken the material turn is that we sometimes treat technological devices as thin objects (Bunker, 2009; Leman-Langlois, 2006; McMullan and Perrier, 2003; Robert and Dufresne, 2008; White and Ready, 2009). We do so in three interrelated ways.…”
Section: From Thin To Thick: Intermediaries and Mediatorsmentioning
confidence: 99%
“…The sample included 242 participants (61 men, 177 women, 4 missing), mean age = 24.6 (SD = 2.87; range [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], enrolled in two public universities in central-northern Italy, divided as follows:…”
Section: Samplementioning
confidence: 99%
“…As a consequence, it often played a crucial role in the criminal investigations portrayed on the show. Some scholars have pointed to the so-called "CSI effect", implying the possible influence of the TV series on the decisions of juries in criminal trials by placing more weight on the forensic evidence produced using DNA testing rather than on other kinds of evidence [22,37,38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation